1988
DOI: 10.1007/bf00569337
|View full text |Cite
|
Sign up to set email alerts
|

The role of insertions/deletions in the evolution of the intergenic region betweenpsbA andtrnH in the chloroplast genome

Abstract: TrnH and the intergenic region between trnH and psbA of the chloroplast genomes of alfalfa (Medicago sativa), Fabaceae, and petunia (Petunia hybrida), Solanaceae, were sequenced and compared to published sequences of that region from other members of those families. A striking feature of these comparisons is the occurrence of insertions/deletions between short, nearly perfect AT-rich direct repeats. The directionality of these mutations in the petunia, tobacco and Nicotiana debneyi lineages within the Solanace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(48 citation statements)
references
References 34 publications
4
44
0
Order By: Relevance
“…As demonstrated in this study, the trnH-psbA region has shown high occurrence of indels even in closely related species (Aldrich et al, 1988;Shaw et al, 2005). trnL and trnL-trnF regions showed hardly any variation, while their adjacent region trnT-trnL seemed to be more informative as noted by previous studies (Shaw et al, 2005).…”
Section: Discussionsupporting
confidence: 80%
“…As demonstrated in this study, the trnH-psbA region has shown high occurrence of indels even in closely related species (Aldrich et al, 1988;Shaw et al, 2005). trnL and trnL-trnF regions showed hardly any variation, while their adjacent region trnT-trnL seemed to be more informative as noted by previous studies (Shaw et al, 2005).…”
Section: Discussionsupporting
confidence: 80%
“…According to the cpDNA restriction map described by Heyraud et al [5], this experiment also allowed the precise location of the tRNA his gene near the right end of the inverted repeat IR(A) of sunflower cpDNA. This result confirms that the region containing these genes on the sunflower cpDNA is also located in a highly conserved position, as in ten other species [1,6,16].…”
Section: Cps T T C G C C C a T G T T A T T A T G A T T T C T T T T T supporting
confidence: 77%
“…There appears to be something about the region near psbA (=5 kb) that is prone to recombination. It may be the direct repeats to either side of psbA (30,31), the hot spot for additions and deletions at the junction of the LSC and IR A (32), and/or the large gene-free sequences that exist between psbA and atpA (10). One capillus-veneris cpDNA are Pst I (e) and EcoRV (A).…”
Section: Methodsmentioning
confidence: 99%